Effects of resistance training on selected healthrelated fitness variables among female students of Universiti Sains Malaysia, Health Campus - Rigar, Carl Sherman (Universiti Sains Malaysia, 2011)
The purpose of this study was to examine the effects of resistance training among female students of Universiti Sains Malaysia, Health Campus on selected health-related fitness variables including body composition, muscular strength, muscular endurance and flexibility. A total of twenty healthy female students of Universiti Sains Malaysia, Health Campus (20.3 ± 0.7 years old) were involved in this study. All subjects underwent pre-test where their anthropometrical measurements, body composition, muscular strength, muscular endurance and flexibility were measured. They were randomly assigned into control group (n=10) and exercise group (n=10). The control group resumed with their normal physical activity while the exercise group underwent resistance training programme which comprised of ten resistance exercises per session, thrice a week. After six weeks, all the subjects underwent post-test to measure their anthropometrical measurements, body composition, muscular strength, muscular endurance and flexibility. The findings revealed no significant difference (p > 0.05) in above measurements between the two groups. Although there were no significant differences, a trend of improvement could be observed in body composition and back and leg strength among exercise subjects after six weeks of resistance training. The results show that resistance training does bring benefits on health-related fitness among female students and it should be made a part of regular exercise apart from aerobic exercise to improve health-related fitness.